THE ROLE OF DIGITAL LITERACY AND PUBLIC EDUCATION IN COUNTERING ARTIFICIAL INTELLIGENCE-BASED POLITICAL DISINFORMATION - R. Yogie Prawira (Branding: Jurnal Manajemen dan Bisnis, 2024)
The rapid development of Artificial Intelligence (AI) technology, such as deepfakes and algorithm-based narratives, has disrupted political communication and threatened the integrity of democracy. This qualitative research aims to explore in depth the role of digital literacy and public education as a public defense strategy against AI-based political disinformation. A descriptive qualitative approach was used to understand how the public interprets, identifies, and responds to the threat of this information manipulation. The results reveal two main findings. First, AI-based political disinformation has been shown to create an illusion of truth. Conventional digital literacy has failed to counter because existing curricula remain stuck in basic functional skills and have not integrated aspects of AI literacy or confirmation bias mitigation. Second, current strategies for countering hoaxes have been reactive through take-down and debunking, thus being outpaced by machine replication. This study concludes that public knowledge strengthening must transition to a proactive approach through pre-bunking. The effectiveness of this downstream strategy must be supported by a collaborative multi-stakeholder governance model at the upstream level, through the implementation of adaptive regulations such as mandatory watermarking of AI content and regular algorithm audits on social media platforms to maintain a digital democracy ecosystem with integrity.